2008
DOI: 10.1124/mol.108.049551
|View full text |Cite
|
Sign up to set email alerts
|

Discovery, Characterization, and Antiparkinsonian Effect of Novel Positive Allosteric Modulators of Metabotropic Glutamate Receptor 4

Abstract: Parkinson's disease (PD) is caused by the death of dopamine neurons in the basal ganglia and results in motor symptoms such as tremor and bradykinesia. Activation of metabotropic glutamate receptor 4 (mGluR4) has been shown to modulate neurotransmission in the basal ganglia and results in antiparkinsonian effects in rodent PD models. N-Phenyl-7-(hydroxyimino)cyclopropa [b]chromen-1a-carboxamide (PHCCC) is a positive allosteric modulator (PAM) of mGluR4 that has been used to further validate the role of mGluR4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
234
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 183 publications
(238 citation statements)
references
References 31 publications
4
234
0
Order By: Relevance
“…Progress has been made on these varying degrees of efficacy; however, the optimal combination is not yet apparent from the current state of the art (vide supra). Indeed, the proper mix of EC 50 , E max , and FS may have vastly different requirements for different disease states, and a significant volume of data and progress are needed in the field before this important issue can be resolved.…”
Section: Mglu4 Ligandsmentioning
confidence: 99%
See 4 more Smart Citations
“…Progress has been made on these varying degrees of efficacy; however, the optimal combination is not yet apparent from the current state of the art (vide supra). Indeed, the proper mix of EC 50 , E max , and FS may have vastly different requirements for different disease states, and a significant volume of data and progress are needed in the field before this important issue can be resolved.…”
Section: Mglu4 Ligandsmentioning
confidence: 99%
“…50 Separation of the isomers showed that the cis-regioisomer 15 (VU0155041) was solely responsible for the potency. Subsequent chiral chromatographic separation of the cis-isomers apparently showed no enantiomeric preference for the receptor.…”
Section: Mglu4 Ligandsmentioning
confidence: 99%
See 3 more Smart Citations